Immunity to Chlamydial Infections of the Eye V. Passive Transfer of Antitrachoma Antibodies to Owl Monkeys - Orenstein, Neil S. (1973)
Previous studies have shown that owl monkeys which have had a trachoma agent infection were subsequently highly resistant to challenge by both homologous and heterologous organisms. In the present study, passive transfer of owl monkey serum containing antitrachoma antibody from immune monkeys did not protect recipient monkeys from infectious challenge with homologous trachoma. Antibody was not detectable in eye secretions of the recipient monkeys until the intensity of infection was waning, suggesting but not proving that local antibody synthesis rather than simple transudation of serum antibody occurs.